DEEPFAKE DAN MANIPULASI VISUAL DALAM KAMPANYE: ANALISIS DAMPAK TEKNOLOGI VISUAL PADA KREDIBILITAS INFORMASI POLITIK - Vito Daryfauzi; Bagaskara Rizqian (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Komputer Indonesia, 2026)
This study aims to understand how visual technology, especially deepfake and visual manipulation, affects the credibility of political information in the digital era, especially during the campaign period. The research approach used is qualitative, with a phenomenological design. The phenomenological method allows for in-depth exploration of the experiences of individuals and groups exposed to visual manipulation in the context of political campaigns. The results of the study provide a more comprehensive understanding of the content of deepfake and visual manipulation in digital political campaigns (identified based on technological modality, compositional modality, and social modality), simulacra in deepfake and visual manipulation in political campaigns on digital media, and the impact of deepfake and visual manipulation on the credibility of political information. Thus, this study contributes to academic discourse and public policy related to the use of visual technology in political campaigns.